Rhododendron javanicum (Blume) Benn. AND Rhododendron sessilifolium J.J. Sm. GERMINATION AND SEEDLINGS DEVELOPMENT ON DIFFERENT GROWING MEDIA AND FERTILIZERS APPLICATION - Rahman, Wiguna; Juairiah, Lina (Buletin Kebun Raya, 2013)
Growing medium is one of the most important factor for ex situ conservation of Rhododendron. Study on different growing media available locally were conducted for germinating and developing the seedlings of Rhododendron javanicum and R. sessilifolium. Tree fern roots medium was suitable for germination and developing Rhododendron javanicum and R. sessilifolium seedlings. Growing medium for bigger seedlings using "Cibodas compost" was better than "Cibodas compost and rice husk" for the development of Rhododendron seedlings. Fertilizer application did not showed significant effect on R. sessilifolium seedlings. However, low concentration of fertilizer was recommended rather than high concentration of fertilizer. Some fertilizers at different applications were tested on the development of R. sessilifolium seedlings.